The Effect of H2O2 and Lactic Acid Addition in Biological Saliva on the Corrosion Behaviour of 304L Stainless Steel. Issue 1 (June 2020) - Simionescu, N; Benea, L; Chiriac, A
Abstract: The aim of this study is to assess the corrosion resistance of SS304L in biological solution (named Ringer) at body temperature 37 0 C. The addition of H2O2 and C3H6O3 simulate the presence of microorganism metabolic product and inflammatory conditions. 304L stainless steel, in the oral cavity, can interact with other product capable of initiating corrosion of metals. H2O2 was used because is delivered by leukocytes and microscopic organism (bacteria) occurs in conditions in which the human body suffers a process of inflammation and lactic acid can be produced by a bacterial strain called Streptococcus mitis meeting in the dental plaque. For corrosion investigations was used in situ measurement (electrochemical) such as: OCP (open circuit potential) and EIS (electrochemical impedance spectroscopy). The electrochemical results conclude that the additions of hydrogen peroxide and lactic acid as well as these two compounds in combination have influence on the corrosion behaviour of SS304L in Ringer saliva.